2015
DOI: 10.1038/srep11802
|View full text |Cite
|
Sign up to set email alerts
|

QiShenYiQi Pills, a compound in Chinese medicine, protects against pressure overload-induced cardiac hypertrophy through a multi-component and multi-target mode

Abstract: The present study aimed to explore the holistic mechanism for the antihypertrophic effect of a compound in Chinese medicine, QiShenYiQi Pills (QSYQ) and the contributions of its components to the effect in rats with cardiac hypertrophy (CH). After induction of CH by ascending aortic stenosis, rats were treated with QSYQ, each identified active ingredient (astragaloside IV, 3, 4-dihydroxy-phenyl lactic acid or notoginsenoside R1) from its 3 major herb components or dalbergia odorifera, either alone or combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 44 publications
2
44
0
Order By: Relevance
“…Furthermore, nitrate tolerance has been demonstrated as the loss of effects on treadmill walking time and time of onset of angina [13]. Therefore, scientists need to explore more safe and effective drugs to treat CHD [14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, nitrate tolerance has been demonstrated as the loss of effects on treadmill walking time and time of onset of angina [13]. Therefore, scientists need to explore more safe and effective drugs to treat CHD [14].…”
Section: Introductionmentioning
confidence: 99%
“…Other study found that 20-HETE has detrimental effects on cardiomyocytes and ECs[38]. The mechanisms of some TCMs, such as ShexiangBaoxin pills, are usually through a multi-target and multi-pathway mode due to different active ingredients [39]. Hence, the roles of 20-HETE on cardiac effect might be related to the dual-directional regulation effects of ShexiangBaoxin pills.…”
Section: Discussionmentioning
confidence: 99%
“…HM, as a major part of traditional Chinese medicine (TCM), has a long history of clinical use in disease treatment, and often uses a variety of herbs in different combinations to strengthen the therapeutic effects (synergistic effects). Moreover, numerous studies have indicated that many Chinese herbs or herbal formulations (composed of multiple herbs) can promote a cure via a multi‐target effect . To restore the dynamic balance among body systems and achieve the best curative effect, herbalists chose a combination of several herbs based on distinct disease presentations.…”
Section: Natural Molecule Discovery From Herbal Medicinementioning
confidence: 99%
“…Moreover, numerous studies have indicated that many Chinese herbs or herbal formulations (composed of multiple herbs) can promote a cure via a multi-target effect. [15][16][17][18][19] To restore the dynamic balance among body systems and achieve the best curative effect, herbalists chose a combination of several herbs based on distinct disease presentations. The combinational formulation usage of HM is the heart of TCM and plays a very important role in the treatment of disease.…”
Section: An Overview Of Herbal Medicinementioning
confidence: 99%